Tem investigation of CuInSe₂-ZnSe heterostructures for thin film solar cells - Grigorov, S.N.; Kosevich, V.M.; Kosmachev, S.M.; Taran, A.V. (Вопросы атомной науки и техники, 2008)
In the article, CuInSe₂ thin films obtained by sequential deposition of Cu and indium selenide starting layer with the further annealing of the two-layered composition in Se atmosphere were investigated by transmission electron microscopy (TEM). On the base of the obtained basic CuInSe₂ layers, the ZnSe buffer layers were grown. It was found that ZnSe layer of cubic modification grow epitaxialy on a surface of CuInSe₂.